2018
DOI: 10.1590/s1517-707620170005.0271
|View full text |Cite
|
Sign up to set email alerts
|

Determinação do módulo de elasticidade da madeira em função da inclinação das fibras utilizando tomógrafo acústico

Abstract: RESUMOOs objetivos deste trabalho são determinar, a partir de ensaios não destrutivos, o módulo de elasticidade em função da inclinação das fibras da madeira através de um tomógrafo acústico, comparar e discutir a aplicação de seis critérios de falha adaptados para ensaios não destrutivos e modificar as equações para determinar os critérios de falha mais adequados para o ensaio não destrutivo proposto. Para isto foram ensaiados 6 corpos de prova de 150x15x4 cm de 6 espécies de madeira. Utilizou-se um tomógrafo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Few studies have been performed to determine the MOEd of a specimen by pulse tomography; most researchers use voltage wave emission or transverse vibration. However, Carrasco et al (2017), who used the acoustic tomograph, concluded that it could be helpful for determining the modulus of elasticity in the fibres by only one experimental test. This work confirms the need to agree on a standard classification for the dynamic method; it is needed because too little is known about these tests of live trees in the Amazon and the values obtained.…”
Section: Dynamic Elasticity Modulusmentioning
confidence: 99%
“…Few studies have been performed to determine the MOEd of a specimen by pulse tomography; most researchers use voltage wave emission or transverse vibration. However, Carrasco et al (2017), who used the acoustic tomograph, concluded that it could be helpful for determining the modulus of elasticity in the fibres by only one experimental test. This work confirms the need to agree on a standard classification for the dynamic method; it is needed because too little is known about these tests of live trees in the Amazon and the values obtained.…”
Section: Dynamic Elasticity Modulusmentioning
confidence: 99%
“…Other studies validated the use of tomography to determine the physical properties of wood, such as resistographic amplitude (Rollo et al, 2013), moisture content (Putri et al, 2017); Latorraca et al, 2011), and mechanical properties (Young and shear modulus) (Gonçalves et al, 2014;Gonçalves et al, 2011;Sedik et al, 2010), elasticity modulus (Carrasco et al, 2017), knots interference, juvenile wood, and reaction wood (Palma et al, 2018). Also, research was carried out to determine the pith´s location (Perlin et al, 2018) and address aspects related to wood anisotropy (Perlin et al, 2019;Arciniegas et al, 2014).…”
Section: Introductionmentioning
confidence: 96%
“…Impulse tomography is based on the propagation of mechanical stress waves generated from hammer shocks (Mendes and Silva Filho, 2019;Carrasco et al, 2017;Castro et al, 2011). The emission and capture of signals, which result in time and distance information, with which propagation speed is calculated, is done by sensors attached to the trunk by metal nails (Heidelberg, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In order to use wood in construction, it is necessary to determine its physical and mechanical properties [21,22] according to specific Standard Codes, such as Brazilian [23] and European [24]. However, when it is impossible to produce specimens [25] or pieces present structural dimensions [26], nondestructive tests are performed by different techniques, including transverse vibration [27,28], acoustic tomography [29] and ultrasound [30]. In addition, it is also possible to estimate wood properties as a function of other known properties using regression models [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%